The Application of Balanced Scorecard as a Strategic Performance Evaluation Tool in Medium-Sized Companies - Nanang Sutrisna; Ifah Rofiqoh (Oikonomia : Journal of Management Economics and Accounting, 2025)
The Balanced Scorecard (BSC) has become increasingly adopted by medium-sized enterprises as a strategic performance evaluation tool capable of integrating financial and non-financial indicators within a unified measurement framework. This study examines the effectiveness of BSC implementation in enhancing strategic performance by identifying success factors, implementation barriers, and integration models within organizational management systems. A Systematic Literature Review (SLR) based on PRISMA guidelines was conducted, involving the identification, screening, eligibility assessment, and inclusion of 24 verified scientific publications from 2014–2024. The findings indicate that the BSC significantly contributes to improving strategic planning, budgeting, internal process efficiency, customer orientation, and organizational learning culture. The study also reveals that successful implementation is strongly driven by leadership commitment, strategic clarity, digital integration, and human resource capability, whereas major barriers include challenges in indicator formulation, limited strategic management literacy, and inconsistent evaluation cycles. The study concludes that the Balanced Scorecard holds substantial potential as a strategic tool for medium enterprises, but its effectiveness depends on consistent integration across all managerial processes..